Accuracy of a fourth generation apex locator-an in vitro evaluation - Dalia Abdullah; Mariam Abdullah (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2007)
The new fourth generation electronic apex locator (EAL), Elements (SybronEndo, USA) has been introduced recently in the market. This study aims to investigate the accuracy of this EAL and to compare the result with a well-known apex locator, Root ZX and the radiographic technique using an in vitro model. Thirty anterior teeth with straight canals stored in 10% formalin were used. Access cavities were prepared followed by coronal flaring of the canals. Water was used as an irrigant. After the actual lengths (AL) were measured, the teeth were then embedded in an alginate model. Periapical radiograph of each tooth was taken using a digital sensor and the radiographic lengths (RL) were measured 0.5 mm short of the radiographic apex. Electronic tooth length measurements (EL) were carried out using both EAL. Canals were then irrigated with 2.5% NaOCl and EL was taken again. Results showed that both EALs were highly accurate to within + 0.5 mm of the apical foramen, with mean differences between the AL and EL of Elements 0.23mm (SE = 0.04) and Root ZX was 0.31mm (SE = 0.05). RL was significantly less accurate compared to the readings from both EAL. No significant difference was found in the reading between both apex locators when measurements were taken in NaOCl solution. Both Elements and Propex proved to be as reliable as Root ZX. Presence of sodium hypochlorite solution did not affect the accuracy of the measurements.